The Association between Relative Age Effect, Goals Scored, Shooting Effectiveness and the Player's Position, and her Team's Final Classification in International Level Women's Youth Handball - Yzan Saavedra; Jose M. Saavedra (Montenegrin Sports Academy, 2020)
The objectives of this study were (i) to determine whether there is a relationship between the relative age effect (RAE) and the final classification of the teams, player's positions, number of goals scored, and shooting effectiveness, and (ii) to determine whether there are differences in the number of goals scored and shooting effectiveness depending on the final classification and player's positions. The study subjects were 380 players who took part in the 2018 Women's Youth World Handball Championship. The independent variables were the relative age effect and the number of goals and shooting effectiveness of each type of shot. The dependent variables were the player's position and the team's final classification. To investigate the relationship between the RAE and the team's final classification, player's position, goals scored, and shooting effectiveness, contingency tables were drawn up and subjected to a chi-squared test. The dependence of the differences in goals and shooting effectiveness on the team's final classification and the player's position was studied by means of an ANOVA with a Tukey post hoc test. For the sample overall, there was no RAE, only an association between the classification and the year of birth, with more players born in the senior year in the teams ranked from 1st to 8th place than in those classified from 9th to 24th place. The teams classified from 1st to 4th had more significant numbers of several variables. There were differences in goals and shooting effectiveness, depending on the player's position.